2020
DOI: 10.1016/j.annonc.2019.11.015
|View full text |Cite
|
Sign up to set email alerts
|

Clinical activity of programmed cell death 1 (PD-1) blockade in never, light, and heavy smokers with non-small-cell lung cancer and PD-L1 expression ≥50%

Abstract: Background: Immune checkpoint inhibitors (ICIs) are standard therapies for patients with advanced non-small-cell lung cancer (NSCLC) and a programmed death-ligand 1 (PD-L1) tumor proportion score (TPS) ≥50%. Tumor mutation burden (TMB) also predicts response to ICIs but is often not available in real time for decision making in the first-line setting. Smoking exposure can be a proxy for TMB in NSCLC. The impact of smoking status on efficacy of PD-1 blockade in NSCLC patients with PD-L1 TPS ≥50% ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
75
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(87 citation statements)
references
References 22 publications
0
75
0
Order By: Relevance
“…Past research has shown that tumor mutation burden (TMB), microsatellite instability (MSI) and PD-L1 expression may predict ICB response in some cancer types [6] , [7] , [8] . However, no biomarker is currently validated to predict resistance or benefit derived from immunotherapy with clinically significant accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…Past research has shown that tumor mutation burden (TMB), microsatellite instability (MSI) and PD-L1 expression may predict ICB response in some cancer types [6] , [7] , [8] . However, no biomarker is currently validated to predict resistance or benefit derived from immunotherapy with clinically significant accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…pneumonitis, but recent studies have found that the occurrence of radiation pneumonitis is also related to the lung function before radiotherapy [16,17]. The incidence of chest cancer treated with radiotherapy and chemotherapy is 40-60% [18,19]. Due to its high incidence, insidious onset, delayed onset, and no targeted treatment, once diagnosed, it is often impossible to reverse the condition.…”
mentioning
confidence: 99%
“…1 Traditional treatment, such as surgical resection, chemotherapy, had obvious limitations in recurrence and distant metastasis. Recently immunotherapy seems to be the potential and effective treatment in various cancers [2][3][4][5][6][7][8][9][10] , including colon cancer 7 . However, only about 20% of patients with cancer have good response to immunotherapy 11 .…”
Section: Introductionmentioning
confidence: 99%